"Mídia, Cultura e Desenvolvimento: Estudo Comparado de Revistas Regionais" - Salomão, Virgínia (2009)
Historically considered as national, the magazine medium has been reinvented in the regions. Its tradicional patterns are going through a readaptation and the dominant schemes in its journalistic production are no longer homogeneous. There is an area movement looking for a new market, embedded in the regional specificities and socio-economic development characteristics that is flourishing in a daily previously unknown by the so-called great press. The Brazilian magazine readers market is growing consecutively in a organized way for years. Although the absence of records in the authority sources, the regional magazines and its editions has been increased in number speedily, despites the financial economical reveses suffering by the other sectors of cultural industry. This phenomenon is the objective of this research: mapping the new geography of the magazine medium in the five Brazilian macro regions to comprehend how the regional identities are processed to the credit of public communication with specific groups, characteristic that is in the essence of magazine. Mixed methods of qualitative and quantitative research design the path to necessary juxtaposition to describe this boom of publications. Multiple cases study and content analysis, involving five magazines from each one of political administrative regions describes and discuss the bias of segmentation in the editorial market beyond the Rio São Paulo axle. As a result of this investigation, it came to the following conclusions: the consolidation of a new journalistic area, professionalized, competent and creative, far from the amateurism, provincialism and to the simplistic imitation; the more significant vehicle of each five infranational macro regions, according to the methodological built created to this research, work with relations, ways and demands of symbolic production without artificialism; the institutionalized regional identities are intimately connected to the regions of influence and the urban nets; the urban life style reproduction stamped in the magazines of this corpus reinforces its own power like a communication vehicle, as well as works like a feedback to the regional accents in the social levels where they are generated and digested.